Rare Tumors in Children and Adolescents – the STEP Working Groupʼs Evolution to a Prospective Registry - Hippert, Felicitas; Desing, Lena; Diez, Sonja; Witowski, Andrea; Bernbeck, Benedikt; Abele, Michael; Seitz, Christian; Erdmann, Friederike; Brecht, Ines; Schneider, Dominik T. (Klinische Pädiatrie, 2021)
Background Very rare tumors (VRT) in children and adolescents have such a low incidence that until recently, they have not been integrated into the clinical and scientific network of pediatric oncology. Data is very limited and consistent treatment strategies are missing. Thus, VRTs are classic orphan diseases. To counteract this problem, the Arbeitsgemeinschaft für Seltene Tumorerkrankungen in der Pädiatrie (STEP) was founded. Here we report on patient recruitment during the first 10 years. Patients Patients aged up to 18 years and not included in any other clinical trial or GPOH registry were included in this analysis. Methods Data was collected from 2008 to 2018 by means of a standardized form. The recorded diagnoses were descriptively analyzed focusing on histology, localization, and year of report. Results A total of 623 patients with VRTs were registered. During 2008–2014, the annual number of registrations was around 40 and is around 90 since 2015. Most frequent diagnoses included tumors of the skin (n=150), tumors of the gastrointestinal tract (n=102), tumors of the gonads (n=77), the ENT region (n=68), and miscellaneous tumors (n=107). Discussion With the establishment of central structures for clinical consultation and documentation of VRTs, the number of registrations increased. Comprehensively, VRTs are as common as other classic pediatric oncology tumors, but extremely heterogeneous in terms of localization, histology, and prognosis. By a centralized and complete registration and analysis of VRTs, also in collaboration with international partners, it is possible to develop treatment strategies and thus greatly increase treatment quality.
Keywords: childhood cancer; rare tumors; epidemiology; melanoma; colorectal carcinoma; registries